1931 N.Y. Laws 1033 - (:unkn) unknown (My University, 1931)
Ch. 435, § 1; Prohibited using an imitation pistol and carrying or possessing a black-jack, slungshot, billy, sandclub, sandbag, metal knuckles, bludgeon, dagger, dirk, dangerous knife, razor, stiletto, imitation pistol, machine gun, sawed off shot-gun, or ay other dangerous or deadly weapon.
Keywords: POSSESSION